Equipment and Facilities Gap in Vocational Technical Education of Higher Institution: Implication for Graduates Employability in Nigeria - Olojuolawe, Sunday; Adeoluwa, Olufemi Victor (Sains Humanika, 2022)
Sains Humanika Full paper Equipment and Facilities Gap in Vocational Technical Education of Higher Institution: Implication for Graduates Employability in Nigeria The global aim of technical education is to produce competent manpower who will be employable or self-reliant. The rising rate of restiveness and criminality occasioned by the spate of unemployment among technical education graduates in Nigeria calls for concern. Despite the huge government investment in technical education, there seem to be a lot of grounds to be covered in equipment and facilities. This study surveys the equipment and facilities used for teaching technical students in Nigeria Universities. A peer-reviewed methodological approach based on a systematic review of journal articles and a checklist of the minimum equipment and facilities standards by the National University Commission was conducted using research assistants from Adekunle Ajasin University, Akungba Akoko, Ekiti State University and the Bamidele Olumilua University of Education, Science and Technology, Ikere-Ekiti was used for this study. The totality of equipment and Facilities available in the 3 Universities for imparting knowledge in Electrical/Electronics, Building technology, Woodwork Technology, Metalwork and Automobile technologies. The percentages of the available equipment and facilities were obtained using Excel Package for generalization. The study reveals that equipment and facilities for some courses in technical education are grossly in short supply. A recommendation was made for further study on the quality and functionality of the equipment and facility for teaching technical students in Nigerian Universities.